Follow-up OAUNI photometry of SN 2024iss - Pereyra, Antonio (2024)
We report new photometry of Type II SN 2024iss gathered with the OAUNI 51cm telescope at Huancayo Observatory, Peru. CCD imaging in R filter was performed on four consecutive nights under non-photometric conditions with the target on higher airmasses. The integration time was 80x20s=1600s in each observation. Our measurements yielded: Date (UT) | filter | seeing (") | mag, 2024-07-03.124 | R | 14.70 +/- 0.02, 2024-07-04.129 | R | 14.72 +/- 0.02, 2024-07-05.112 | R | 14.76 +/- 0.01, 2024-07-06.097 | R | 14.77 +/- 0.01. UCAC4 field stars were used for the zero point calibration. Our observations are ~7.3 weeks after the GOTO detection. The OAUNI project is supported by UNI, TWAS, IGP and ProCiencia-Concytec (Convenio 133-2020 Fondecyt).